Protective Role of L-3-n-Butylphthalide in Cognitive Function and Dysthymic Disorders in Mouse With Chronic Epilepsy - Ye, Xiaowen; Rong, Zhouyi; Li, Yanfang; Wang, Xintian; Cheng, Baoying; Cheng, Yiyun; Luo, Haijuan; Ti, Yue; Huang, Xiaohua; Liu, Zhaoji; Zhang, Yun-wu; Zheng, Weihong; et al. (Frontiers in Pharmacology, 2018)
Epilepsy is a common neurological disease with recurrent seizures and neurobehavioral comorbidities, including cognitive impairment and psychiatric disorders.Recent studies suggest that L-3-n-butylphthalide (NBP), an extract from the seeds of Apiumgraveolens Linn (Chinese celery), ameliorates cognitive dysfunction in ischemia and/or Alzheimer's disease (AD) animal models. However, little is known about the role of NBP in epilepsy and the associated comorbidities. Here, using a pilocarpine-induced chronic epileptic mouse model, we found that NBP supplement not only alleviated seizure severity and abnormal electroencephalogram (EEG), but also rescued cognitive and emotional impairments in these epileptic mice.The possible underlying mechanisms may be associated with theprotective role of NBP in reducing neuronal loss and in restoring the expression of neural synaptic proteins such as postsynaptic density protein 95 (PSD95) and glutamic acid decarboxylase 65/67 (GAD65/67). In addition, NBP treatment increased the transcription of neuroprotective factors, brain-derived neurotrophic factor (BDNF) and Klotho.These findings suggest that NBP treatment may be a potential strategy for ameliorating epileptogenesis and the comorbidities of cognitive and psychological impairments.